KERJASAMA CHINA DAN NEGARA-NEGARA BALKAN MELALUI 16+1 FRAMEWORK - Dendy Rizki Feriansyah; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The 16 + 1 format is a cooperative platform for China and Eastern and Central Europe including the Balkan countries. Through this instrument China expanded its influence into the Balkan countries by investing in the development of transportation and energy infrastructure. China’s investment has some characteristic and polemic. This research aims to describe how the model of China's investments in the Balkan countries through a 16 + 1 framework. The study used the perspective of Neo-Marxism, in the capitalist global economic system, the central state could impose an unbalanced exchange and cause various problems in periphery countries. This Research used descriptive qualitative research methods which is the research data was obtained through literature review and library research. The level of analysis in the study were nations that focusing on describing Chinese patterns in investing and the concept used in this research was the concept of dependency. The result of this study indicate that the involvement of China's political-based financial institutions, project implementation by Chinese construction firms, and the acquisition as form of market extensionand equity capital are Chinese patterns in investing that will be described in the this research.  Keywords: 16+1 platforms, Balkan countries, China, investment development, neo-Marxism, regional cooperative, unbalanced exchanges